A guarda compartilhada frente ao princípio do melhor interesse da criança e do adolescente - Coelho, Adriana Lopes Mair (2016)
Nowadays the family entities live with the hard reality of dissolution of marriage/common-law marriage. Whenever this situation becomes real, a rearrangement in the family structure is necessary. When there are children, that reality can be, in many cases, a tortuous path - in which many prefer not to walk, because in these paths is required coping with different feelings. Disruption of conjugality ends in interfering with parenting, generating conflicts of difficult solution. When this occurs and families can’t get a consensus, the State comes to decide on the new family arrangements. Unnecessary to say that this decision is not always liked by the parties involved. The objective of this research was to determine whether the principle of the best interest of the child and adolescents is used to support the decisions of the judges in the application of joint custody and also to bring to light if this principle is used indiscriminately for lack of a clear concept and defined limits. For this purpose, data from the courts of justice of the states of Paraná and Rio Grande do Sul has been collected, analysed and cataloged in a file composed of 14 items. The results indicate that this is the most used fundament, in which 92% of the decisions that apply or deny shared custody. The results show that: yes, this principle (best interest of the child and adolescents) is the most used in decisions – for implementing joint custody or refusing it. The new constant normative guidance in Law 13.058/2014, which makes the shared custody rule even in the event of conflict between the parents, it is still used in a cautious way by the judges. The measure resulted in a greater incidence on the use of the principle of the best interest of reasons for the decision in relation to the period in which the Law 11.698/2008 was still valid. About the psychosocial report, there is still the need for maturing the importance of interdisciplinarity. Only 34% of the judged attest to the influence of the psychosocial report on the decision, showing that those reports have not yet been widely used within the decision-making process. According to the data, the reports still do not hold a proper position within the decision-making process. The interface between law and other areas of knowledge such as Psychology and Social assistance needs to be a reality in the solution of conflicts in the family specialized courts.